Assessment of Some Physical and Chemical Characteristics in Three Sunflower Varieties - Aziz, Hussein M. (Sulaimani Journal for Pure and Applied Sciences, 2016)
A field experiment was conducted in Kanipanka station, at a research center, which belongs to the Ministry of Agriculture and located about 36 Km south-east of Sulaimany,the planting was done in autumn at (July 01, 2012). A laboratory experiment was conducted to estimate some physical and chemical characteristics such as seed volume, true density, water absorption capacity, water absorption index, seed size, oil%, ash%, nitrogen%, potassium%, calcium% and protein% in different varieties of sunflower (Confute, Flame and Local). The results demonstrated the existence of significant differences (at P>0.05) among studied varieties for all physical and chemical characteristics except thousand seed weight. The results of physical properties exhibited that Local variety had maximum values of seed volume, seed size, water absorption capacity and water absorption index. Concerning the chemical properties of seeds, the results showed that Confute variety gave high amount of nitrogen, potassium, protein and oil. The correlation coefficients of some seed related traits showed that oil content of the seeds was significantly and negatively related to seed size, protein content and ash, but significant and positive relation observed between the oil content and the thousand seed weight.
Keywords: Sunflower; Physical parameters; Chemical parameters